2007
DOI: 10.1080/10428190701494520
|View full text |Cite
|
Sign up to set email alerts
|

CD40 expression identifies a prognostically favourable subgroup of diffuse large B-cell lymphoma

Abstract: In order to confirm our earlier findings of the prognostic effects of CD23 and CD40 expression in diffuse large B-cell lymphoma (DLBCL), possibly due to association with the germinal center (GC) phenotype and/or an increased autologous tumour response, tumour specimens from 125 patients with de novo DLBCL were investigated for immunohistochemical expression of CD23, CD40, BCL6, CD10, MUM1, CD4 and CD8. CD40 was positive in 64% and was associated with improved overall survival (p = 0.03). A GC phenotype was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
1
20
1
1
Order By: Relevance
“…Our results demonstrate a potential prognostic advantage of CD40 expression even after the incorporation of rituximab to lymphoma therapies. The finding is in accordance with our previous observations regarding the prognostic importance of CD40 in DLBCL [3,4] using a cut-off level of 10%, although in the present series, this was not independent of IPI category.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results demonstrate a potential prognostic advantage of CD40 expression even after the incorporation of rituximab to lymphoma therapies. The finding is in accordance with our previous observations regarding the prognostic importance of CD40 in DLBCL [3,4] using a cut-off level of 10%, although in the present series, this was not independent of IPI category.…”
Section: Discussionsupporting
confidence: 81%
“…Trials with CD40 agonists in B-cell malignancies and solid tumors have shown promising results [16]. A possible mechanism is increased antigen presentation followed by enhanced T-cell response directed against tumor antigens [17], although we observed no correlation between CD40-positivity and high amount of tumor infiltrating T-cells in DLBCL in an earlier study [4].…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Three 0AE6 mm-diameter core biopsies were punched out from the representative areas of each paraffin block and positioned in a recipient paraffin block using a custom-made precision instrument. As TMA might be less reliable for evaluating degree of infiltrating T-cells (Linderoth et al, 2007), OTS was also used when available.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…[3][4][5][6][7][8] Other biomarkers that are being investigated include p53 9,10 and Ki-67 11,12 for breast cancer, Bcl-2 for melanoma, 13 the epidermal growth factor receptor for lung cancer, 14 apoptotic protease activating factor-1 15 for colorectal cancer, and CD23 and CD40 for lymphoma. 16 The most commonly used technique to evaluate tissue-based biomarkers is immunohistochemistry (IHC), owing to its relatively low cost and increased time efficiency over other methods, such as ligand-binding assays 17,18 or fluorescence in situ hybridization. 19 Immunohistochemistry assessment is typically performed by pathologists using optical microscopy, although digital microscopy is increasingly, albeit slowly, being adopted in practice, [20][21][22] following the path of radiology.…”
mentioning
confidence: 99%